Underwater Acoustic Environment of Coastal Sea With Heavy Shipping Traffic: NE Baltic Sea During Wintertime - Syrjälä J; Kalliola R; Pajala J (Frontiers Research Foundation, 2022)
Shipping is the most pervasive source of anthropogenic underwater continuous noise
and local intermittent noise. This study focused on the separation of anthropogenic
intermittent noise from dynamic background noise in the Gulf of Finland using an
adaptive threshold level (ATL) technique. The intermittent noise was validated with
Automatic Identification System (AIS) data and the background noise with selected
environmental factors. Separated components were characterized and compared with
a sound exposure level (SEL) in three 1/3 octave bands. Intermittent noise can be
separated with ATL in the Baltic Sea, and vessel traffic identified as the primary source.
Background noise varies spatially and is partially explained by environmental factors.
Intermittent noise has strong persisting influence on the acoustic environment near
shipping lanes, elevating the SEL in each of the 1/3 octave bands: by 20–30 dB in
the 63 Hz band, by 13–22 dB in the 125 Hz band and by 5–8 dB in the 2000 Hz
band. We conclude that strong intermittent noise is characteristic to the underwater
acoustic environment in the study area with heavy shipping traffic. By combining ATL
with data from AIS, intermittent noise peaks in underwater hydrophone recordings can
be associated with passages of individual vessels.
Keywords: underwater noise, shipping, AIS, adaptive threshold level, Baltic Sea, intermittent noise, noise
threshold